2014
DOI: 10.1111/jgh.12615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical characteristics and prognostic factors of gastrointestinal mucosa‐associated lymphoid tissue (MALT) lymphoma

Abstract: The clinical characteristics and outcomes demonstrated no significant differences between gastric and intestinal tract MALT lymphomas. Serum lactate dehydrogenase level was an independent prognostic factor for the survival of GI MALT lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…6 Elevated LDH levels and poor ECOG PS have been correlated with shorter survival in MALT lymphomas. 34,35 Several retrospective series indicated that lymph node involvement is an important prognostic factor, and some have also suggested that the concomitant involvement of multiple mucosal sites, despite being relatively common, does not necessarily carry an unfavorable impact on outcome. 13,16,36,37 In the original IPI analysis, age was dichotomized at 60 years because this represented the eligibility cut point for myeloablative therapy and autologous stem cell transplant, which was restricted to younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Elevated LDH levels and poor ECOG PS have been correlated with shorter survival in MALT lymphomas. 34,35 Several retrospective series indicated that lymph node involvement is an important prognostic factor, and some have also suggested that the concomitant involvement of multiple mucosal sites, despite being relatively common, does not necessarily carry an unfavorable impact on outcome. 13,16,36,37 In the original IPI analysis, age was dichotomized at 60 years because this represented the eligibility cut point for myeloablative therapy and autologous stem cell transplant, which was restricted to younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…H20084191) was injected into the antecubital vein at a dose of 1.5 mL/kg and a speed of 3.5 mL/s. The delayed contrast enhanced CT scan was performed at 26-180 s after the injection of the contrast [9][10][11][12]. The data of ROI were transmitted to the workstation for analysis and processing.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of validated prognostic factors is an important tool in MALT lymphoma because of their potential impact on survival and management. Several baseline variables have been shown to have prognostic relevance including age, gender, stage, international prognostic index (IPI) score, 8 lactate dehydrogenase (LDH) level, 9,10 immunohistochemical molecules 11 (FOXP1, p53, and BCL2), and localization of MALT lymphoma 12 ; however, most of these have not been validated in studies with large cohorts of patients and remain controversial. Recently, Theiblemont et al 13 generated a MALT prognostic index from the dataset of the IELSG-19 trial; they identified elevated serum β2-microglobulin levels, the presence of B symptoms (fever, night sweats, and weight loss), and male sex as prognostic factors for recurrence-free survival and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%